Visualisation of the local electrochemical activity of thermally-sprayed anti-corrosion coatings using scanning electrochemical microscopy - Walsh, D.A.; Li, Lisa E.; Bakare, M.S.; Voisey, K.T. (Elsevier, 2009)
Scanning electrochemical microscopy was used to probe the local electrochemical activity of anti-corrosion coatings formed from Inconel 625, a Ni-Cr-Mo alloy commonly used in engineering applications. The coatings were formed using a high velocity oxygen fuel thermal spraying technique. Upon spraying onto mild steel substrates, clear splat boundaries were formed at the interface between droplets of the alloy as they cooled on the substrate surface. Scanning electrochemical microscopy in the feedback mode, employing ferrocenemethanol as redox mediator, was used to determine the local electrochemical activity of samples of the wrought alloy, the sintered alloy and the thermally-sprayed coating. Significantly, the wrought and sintered materials generally showed responses typical of those expected for a purely insulating material. However, feedback approach curve data showed that the electrochemical activity of the entire thermally-sprayed coating was higher than that of the bulk alloy. Local variations in the coating’s activity were then visualised using scanning electrochemical microscopy. These observations indicate that the spraying process increases the conductivity of Inconel 625 and that localised regions of increased electrochemical activity are generated throughout the material, which appear to be related to the splat boundaries formed during spraying.